2021
DOI: 10.1080/09513590.2021.1878133
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells (hUCMSCs) promotes the recovery of ovarian function in a rat model of premature ovarian failure (POF)

Abstract: Human umbilical cord mesenchymal stem cells (hUCMSCs) promotes the recovery of ovarian function in a rat model of premature ovarian failure (POF), Gynecological Endocrinology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The levels of sex hormones, oestrous cycle, and reproductive potential of the treated rats were recovered to some extent, and some transplanted rats even recovered fertility. Other studies also showed the positive effects of hUCMSCs on premature ovarian failure and ovarian dysfunction in a rat model ( 60 , 61 , 62 , 63 , 64 ). In the current study, hUCSC was better than all groups in terms of intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 82%
“…The levels of sex hormones, oestrous cycle, and reproductive potential of the treated rats were recovered to some extent, and some transplanted rats even recovered fertility. Other studies also showed the positive effects of hUCMSCs on premature ovarian failure and ovarian dysfunction in a rat model ( 60 , 61 , 62 , 63 , 64 ). In the current study, hUCSC was better than all groups in terms of intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 82%
“…Zhang et al. demonstrated that HUCMSCs transplantation improves the disorder of sexual cycle, modulates the serum hormone expression to a better state and restores ovarian function in a rat model of premature ovarian failure with no severe adverse effects [ 36 ]. To verify the immunogenicity of allogeneic MSCs, we injected HUCMSCs isolated from human umbilical cord into the right gastrocnemius muscle of nude mice and KM mice.…”
Section: Discussionmentioning
confidence: 99%
“…The third method is stem cell delivery. Mesenchymal stem cells (MSCs) treatment in POF increased the number of follicles, restored plasma sex hormone levels (Zhang et al, 2021b), reduced ovarian inflammation and reduced granulosa cell apoptosis (Ling et al, 2017;Deng et al, 2021). Stem cells are mainly administered by caudal intraperitoneal injection or ovarian orthotopic injections Woo et al, 2012).…”
Section: The Application Of Hydrogels In Pofmentioning
confidence: 99%